Apakah Informasi non-Keuangan berguna bagi Investor: Survei Persepsi bagi Investor Retail di Indonesia - Muhammad Ikbal (Faculty of Economics and Business Mulawarman University, 2017)
Currently investors in decision-making is more likely to use the company's financial statements, on the other side, they had appeared change the view that the non-financial information is more important and is already quite widely used by investors. This current study aims to examine the needs of non-financial information by investors. In This Research we uses survey Online to explore 113 respondents to dig up information on how they use non-financial information in the framework of the investment decision, the results showed that the use of performance information economy in the subsector information Market share and product innovation is predominantly used, then stage the second respondent uses information of employee satisfaction and customer satisfaction. Then the corporate governance seems very frequently used by respondents in the decision making elements of information governance as Director Independence Standards, changes in information control, auditing, ethical guidelines and information strategy management control system. Then to CSR shows the use of information that is at least in general, with the use of most existing information on the items Products Safety Information. This study contributes to the practitioner, especially investors in making investment decisions.Keywords: non-financial information, performance information economy, corporate governance, CSR